(untitled) (Practicum Psychologia, 2025)
This paper proposes the integration of the Model of Culture Fit proposed by Aycan, Kanungo & Sinha (1999) with the Path-Goal Theory of Leadership developed by House (1971) and Locke’s (1968) Goal Setting Theory. The Culture Fit Model explains human resource practices of leaders on the basis of organizational culture variables without considering the impact of societal culture and values in initiating human resource practices. The Path-Goal Theory conceptualizes the leader’s role as that of providing direction and support for employees in attaining their goals and those of the organization. Goal Setting Theory proposes that intentions and goals of individuals determine their performance. Conceptual parallels that seek to explain employee performance on the bases of culture, leadership style and goal setting are identified and interaction effects among the various dimensions analyzed. The resulting model of leadership and organizational performance proposed in this paper examines the interconnectedness of societal culture and values, leadership and motivation in relation to performance in organizations. The integration of the models should therefore further understanding of the social and cultural processes that enhance organizational performance, Implications for theory and practice as well as directions for future research are presented.